Preparation method and application of core-shell structured nano-copper coated micron aluminum
By using the reducing properties of aluminum itself in the alkaline solution, the copper ions are reduced to nanocopper and uniformly coated on the surface of micron aluminum powder, the problem of adding additional agents in the replacement reduction method is solved, and the preparation of high-performance nanocopper coated aluminum powder is realized, which simplifies the process and reduces costs.
Patent Information
- Application Number
- CN202411745597.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-02
AI Technical Summary
In the process of copper-coated modified aluminum powder by using the replacement reduction method, reducing agents, protective agents or complexing agents need to be added, which increases the operational complexity and preparation cost.
In the alkaline solution, the copper ions are reduced to nanocopper by using the reducing properties of aluminum itself and uniformly coated on the surface of the micron aluminum powder to prepare nanocopper coated micron aluminum with a core-shell structure without adding reducing agents, complexing agents or protective agents.
The preparation of nano-copper-coated micro-aluminum with high-performance core-shell structure is realized, which improves the active aluminum content and oxidative heat exogenous, simplifies the process flow, reduces costs, and improves the combustion activity and catalytic performance of aluminum powder.
Smart Images

Figure CN119216599B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of energetic materials, and more particularly to a preparation method and application of core-shell structured nano-copper coated micron aluminum. Background Art
[0002] Aluminum powder is one of the most widely used metal powders in energetic materials such as solid rocket propellants, thermite and explosives. The addition of aluminum powder can effectively improve the combustion efficiency and total energy output of propellants, making it a core component for improving propellant performance. However, as an active metal, aluminum powder is very easy to agglomerate and react with oxygen and water in the air to form a passivation layer (Al2O3), which hinders its dispersion and homogenization in the system and reduces the burning rate and energy density of aluminum-based solid propellants.
[0003] To solve this problem, researchers used surface coating modification technology to treat aluminum powder. Transition metals have good dispersibility and reactivity. When used in solid propellants, they can effectively adjust the decomposition temperature and combustion pressure index of composite propellants. Among them, the copper coating layer can not only prevent the surface oxidation of aluminum powder, but also has a good catalytic effect on the combustion and decomposition of ammonium perchlorate (AP), effectively improving the catalytic ability of single aluminum powder to AP.
[0004] At present, there are many methods for copper-coated modified aluminum powder, mainly electroplating, chemical plating, sol-gel and mechanical alloying. However, these methods generally have disadvantages such as complex process, high cost and low yield. In contrast, the replacement reduction method can further optimize the process flow. For example: Cheng Zhipeng et al. published "Preparation of Core-Shell Structured Cu / Al Composite Particles by Replacement Method", which uses gelatin as a protective agent and fluoride ions as a chelating agent to achieve rapid deposition of copper on the surface of aluminum powder; however, this method still requires the addition of protective agents and aluminum ion chelating agents, which increases the complexity of the operation and the preparation cost. Patent CN108687359A discloses a method for preparing a nano-copper-coated aluminum composite material, which uses a double chelating agent trisodium citrate and ammonium fluoride to prepare composite particles. Although this method can prepare nano-scale copper-coated aluminum powder, the preparation process is cumbersome and requires multiple steps. In addition, the use of trisodium citrate and ammonium fluoride as copper and aluminum ion chelating agents increases the process steps and costs. Li Tingrun et al. prepared Cu / by liquid phase reduction. μ Al composite particles, this process requires the addition of two reducing agents, formaldehyde and hydrazine hydrate, to promote the reaction, and the post-processing operation is cumbersome. Summary of the invention
[0005] Technical problem to be solved: In the process of copper-coated modified aluminum powder by replacement reduction method, in order to obtain copper-coated aluminum composite particles, it is necessary to add a reducing agent, a protective agent or a complexing agent.
[0006] The invention reduces copper ions to nano copper by utilizing the reducing property of aluminum itself in an alkaline solution without adding a reducing agent, a complexing agent and a protective agent, and makes the nano copper uniformly coated on the surface of micron aluminum powder to prepare nano copper coated micron aluminum with a core-shell structure.
[0007] One of the purposes of the present invention is to provide a method for preparing core-shell structured nano-copper coated micron aluminum.
[0008] The preparation method comprises: mixing suspension A and suspension B, stirring evenly at 35-75° C., adding sodium hydroxide and reacting for 3-4 hours;
[0009] The suspension A is an organic suspension of copper acetylacetonate;
[0010] The suspension B is an organic suspension of micron aluminum powder.
[0011] After adding sodium hydroxide, the pH of the reaction system is 10~11. The alkaline environment deprives the Al2O3 film on the surface of the aluminum powder, exposing the active aluminum powder. The reducing property of the aluminum powder itself is used to carry out a replacement reaction between the copper ion solution and metallic aluminum.
[0012] The organic solvent used in the suspension A is one or more of anhydrous ethanol, ethylene glycol, and acetone, preferably anhydrous ethanol.
[0013] The organic solvent used in the suspension B is one or more of anhydrous ethanol, ethylene glycol, and acetone, preferably anhydrous ethanol.
[0014] The mass ratio of the copper acetylacetonate to the micron aluminum powder is 1:0.3-0.6, preferably 1:0.31-0.55, and more preferably 1:0.31.
[0015] The mass ratio of the sodium hydroxide to the micron aluminum powder is 1:0.7-1.3, preferably 1:0.71-1.28. The change in the amount of the sodium hydroxide relative to the micron aluminum powder will affect the morphology of the product, and then affect the activity of the product. If the amount of sodium hydroxide is too low, the aluminum oxide on the surface of the micron aluminum powder will not be completely removed, which will lead to an unsatisfactory morphology of the product; at the same time, the residual aluminum oxide on the surface of the micron aluminum powder will also hinder further reaction, affecting the reaction rate and uniformity of the product. If the amount of sodium hydroxide is too high, although the aluminum oxide film can be completely removed, the excess sodium hydroxide will cause excessive corrosion to the aluminum powder, reduce the reaction activity of the aluminum powder, and cause mass loss of the product, which will eventually lead to a decrease in the oxidation heat release of the product. As a preferred embodiment, the mass ratio of the sodium hydroxide to the micron aluminum powder is 1:0.8.
[0016] In the reaction system, adding too much organic solvent will lead to a decrease in the concentration of sodium hydroxide, and the aluminum oxide film on the surface of the aluminum powder cannot be completely removed, resulting in incomplete reaction. Therefore, as a preferred embodiment, in the suspension A, the mass ratio of the organic solvent to copper acetylacetonate is 1:0.05-0.3, preferably 0.09-0.26; in the suspension B, the mass ratio of the organic solvent to micron aluminum powder is 1:0.04-0.1, preferably 1:0.04-0.08.
[0017] In the above preparation method, adding sodium hydroxide once will make the reaction rate too fast, and single copper will be generated quickly and in large quantities, so that the single copper cannot be coated on the surface of aluminum powder in time and evenly, and self-agglomeration will occur; adding sodium hydroxide twice can make the reduction reaction slower, so that the generated copper can evenly form a coating layer on the surface of aluminum powder, reducing the occurrence of agglomeration. Therefore, as a preferred solution, the sodium hydroxide is added twice.
[0018] When the sodium hydroxide is added twice, the first addition of a larger amount of sodium hydroxide can provide a higher alkaline environment at the initial stage of the reaction, so that the oxide film on the surface of the aluminum powder is removed, and the aluminum-copper replacement reaction begins. The second addition of a smaller amount of sodium hydroxide can slow down the reaction rate, so that the reduced elemental copper is slowly deposited on the surface of the aluminum powder, enhance the uniformity and density of the coating layer, and reduce the agglomeration of nano-copper particles. Therefore, as a preferred embodiment, the amount of sodium hydroxide added for the first time accounts for 3 / 8-3 / 4 of the total amount of sodium hydroxide, such as 3 / 8, 1 / 2, 3 / 4; more preferably 3 / 4.
[0019] After the first addition of sodium hydroxide, the reaction is allowed to proceed for 1-1.5 hours; after the second addition of sodium hydroxide, the reaction is allowed to proceed for 2-2.5 hours.
[0020] The preparation method, one of the schemes comprises the following steps:
[0021] (S1) dispersing copper acetylacetonate in anhydrous ethanol to obtain a suspension A;
[0022] (S2) dispersing micron aluminum powder in anhydrous ethanol to obtain a suspension B;
[0023] (S3) Suspension A and suspension B are mixed and stirred at 35-75°C to form suspension C;
[0024] (S4) maintaining 35-75° C., adding sodium hydroxide to the suspension C twice, stirring and reacting for 1-1.5 hours after the first addition of sodium hydroxide, and stirring and reacting for 2-2.5 hours after the second addition of sodium hydroxide, to form a suspension D;
[0025] (S5) Centrifuging the suspension D, washing with alcohol, and drying to obtain the core-shell structured nano-copper coated micron aluminum; the drying temperature is preferably 65-80°C.
[0026] The second object of the present invention is to provide a core-shell structured nano-copper coated micron aluminum prepared by the preparation method described in the first object of the invention.
[0027] The core of the core-shell structure nano copper coated micron aluminum particle is micron aluminum, and the shell is a nano copper coating layer, and the thickness of the nano copper coating layer is about 0.3-0.5 μ m.
[0028] The specific surface area of the core-shell structure nano-copper coated micron aluminum can reach 28.83m 2 / g.
[0029] The core-shell structure nano copper coated micron aluminum particles have a particle size of 0.02-3.24 μ m, particle size distribution is 1.6-2.8 μ m.
[0030] The core-shell structured nano copper-coated micron aluminum particles are spherical, and the sphericity rate is above 95%.
[0031] Compared with micron aluminum powder, the active aluminum content of the core-shell structure nano copper coated micron aluminum is increased by 7%-22%. The active aluminum content refers to the percentage of aluminum that can be oxidized in the composite material. In the present invention, the active aluminum content is calculated by thermogravimetric analysis.
[0032] The heat release of the core-shell structured nano-copper coated micron aluminum can be as high as 16.72 kJ / g; compared with micron aluminum powder, the heat release of the core-shell structured nano-copper coated micron aluminum is increased by 7.44-10.82 kJ / g.
[0033] The third object of the present invention is to provide an application of the core-shell structured nano-copper coated micron aluminum prepared according to the first object of the invention or the core-shell structured nano-copper coated micron aluminum provided according to the second object of the invention in the fields of solid rocket propellants, aerospace and military industry.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The present invention adopts a replacement reduction method, utilizes the reducing property of aluminum itself, and prepares high-performance core-shell structured nano copper coated micron aluminum (hereinafter referred to as composite particles) by a simple one-pot method. The method only requires copper acetylacetonate, aluminum powder and sodium hydroxide as raw materials, and anhydrous ethanol as solvent; no additional non-propellant components such as reducing agents, complexing agents, surfactants or protective agents are required, and the compatibility between the composite particles and the propellant components can be improved.
[0036] The preparation method of the present invention optimizes the addition of sodium hydroxide and the amount of sodium hydroxide added. Adding sodium hydroxide in batches can avoid the agglomeration of the generated nano copper due to too fast reaction, thereby improving the reduction efficiency of the nano copper. In addition, adding sodium hydroxide in batches can make the reduced nano copper particles more evenly coated on the surface of the aluminum powder.
[0037] The preparation method of the present invention has simple post-processing, making the preparation process of copper-coated aluminum powder more simple and efficient. This simple and efficient preparation method not only reduces costs, but also reduces environmental burden, greatly improves the feasibility of the process, and has wide industrial application potential.
[0038] The composite particles prepared by the optimized preparation process of the present invention can not only effectively prevent the oxidation of the aluminum powder surface, reduce the formation of the passivation layer (aluminum oxide), and improve its oxidation resistance, but also increase the active aluminum content and the oxidation heat release of the aluminum powder, thereby improving the combustion activity of the aluminum powder and the catalytic performance to AP, and optimizing the combustion performance and energy output of the propellant. In addition, the composite particles prepared by the present invention also show good compatibility with other components of the propellant. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the XRD pattern of the core-shell structured nano-copper coated micro-aluminum prepared in Example 1;
[0040] Figure 2 This is a SEM image of the raw material micron aluminum used in Example 1;
[0041] Figure 3 This is a SEM image of the core-shell structured nano-copper coated micron aluminum prepared in Example 1;
[0042] Figure 4 DSC curves of micron aluminum and core-shell structure nano-copper coated micron aluminum prepared in Example 1;
[0043] Figure 5 TG curves of micron aluminum and core-shell structure nano-copper coated micron aluminum prepared in Example 1;
[0044] Figure 6 The DSC curves of pure ammonium perchlorate (AP) and the DSC curves of AP after adding the core-shell structure nano-copper coated with micron aluminum prepared in Example 1 ( n Cu / μ DSC curve of Al-AP);
[0045] Figure 7 This is a SEM image of the core-shell structured nano-copper coated micron aluminum prepared in Example 7;
[0046] Figure 8This is a SEM image of the core-shell structured nano-copper coated micron aluminum prepared in Example 8;
[0047] Fig. 9 This is the SEM image of the product prepared in Comparative Example 1. DETAILED DESCRIPTION
[0048] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0049] The reagents used in the following examples and comparative examples are all commercially available products.
[0050] Copper acetylacetonate was from Shanghai MacLean Biochemical Co., Ltd.;
[0051] Micron aluminum powder was from Shanghai Pantian Powder Material Co., Ltd.;
[0052] Anhydrous ethanol was from Tianjin Xinbote Chemical Co., Ltd.;
[0053] Sodium hydroxide was obtained from Tianjin Fengchuan Chemical Reagent Technology Co., Ltd.
[0054] Example 1
[0055] (S1) 2.06 g (7.87 mmol) of copper acetylacetonate was added to 10 mL of anhydrous ethanol to form a suspension A;
[0056] (S2) 0.64 g (23.70 mmol) of micron aluminum powder (hereinafter referred to as μ A1) was added into 10 mL of anhydrous ethanol to form suspension B;
[0057] (S3) Pour suspensions A and B into a three-necked flask, maintain a constant temperature of 75°C in a water bath and stir for 10 min to form suspension C;
[0058] (S4) adding 0.6 g of sodium hydroxide to suspension C, stirring and reacting for 1 h to form suspension D;
[0059] (S5) 0.2 g of sodium hydroxide was added to the suspension D, and the mixture was stirred for reaction for 2 h, and then centrifuged, washed with anhydrous ethanol, and dried at 80° C. to obtain a core-shell structured nano-copper coated micro-aluminum.
[0060] Example 2
[0061] (S1) 2.06 g (7.87 mmol) of copper acetylacetonate was added to 10 mL of anhydrous ethanol to form a suspension A;
[0062] (S2) 0.64 g (23.70 mmol) μ Al was added to 10 mL of anhydrous ethanol to form suspension B;
[0063] (S3) Pour suspensions A and B into a three-necked flask, maintain a constant temperature of 35°C in a water bath and stir for 10 min to form suspension C;
[0064] (S4) adding 0.6 g of sodium hydroxide to suspension C, stirring and reacting for 1 h to form suspension D;
[0065] (S5) 0.2 g of sodium hydroxide was added to the suspension D, and the mixture was stirred for reaction for 2 h, and then centrifuged, washed with anhydrous ethanol, and dried at 80° C. to obtain a core-shell structured nano-copper coated micro-aluminum.
[0066] Example 3
[0067] (S1) 2.06 g (7.87 mmol) of copper acetylacetonate was added to 10 mL of anhydrous ethanol to form a suspension A;
[0068] (S2) 0.64 g (23.70 mmol) μ Al was added to 10 mL of anhydrous ethanol to form suspension B;
[0069] (S3) Pour suspensions A and B into a three-necked flask, maintain a constant temperature of 45°C in a water bath and stir for 10 min to form suspension C;
[0070] (S4) adding 0.6 g of sodium hydroxide to suspension C, stirring and reacting for 1 h to form suspension D;
[0071] (S5) 0.2 g of sodium hydroxide was added to the suspension D, and the mixture was stirred for reaction for 2 h, and then centrifuged, washed with anhydrous ethanol, and dried at 80° C. to obtain a core-shell structured nano-copper coated micro-aluminum.
[0072] Example 4
[0073] (S1) 2.06 g (7.87 mmol) of copper acetylacetonate was added to 10 mL of anhydrous ethanol to form a suspension A;
[0074] (S2) 0.64 g (23.70 mmol) μ Al was added to 10 mL of anhydrous ethanol to form suspension B;
[0075] (S3) Pour suspensions A and B into a three-necked flask, maintain a constant temperature of 55°C in a water bath and stir for 10 min to form suspension C;
[0076] (S4) adding 0.6 g of sodium hydroxide to suspension C, stirring and reacting for 1 h to form suspension D;
[0077] (S5) 0.2 g of sodium hydroxide was added to the suspension D, and the mixture was stirred for reaction for 2 h, and then centrifuged, washed with anhydrous ethanol, and dried at 80° C. to obtain a core-shell structured nano-copper coated micro-aluminum.
[0078] Example 5
[0079] (S1) 2.06 g (7.87 mmol) of copper acetylacetonate was added to 10 mL of anhydrous ethanol to form a suspension A;
[0080] (S2) 0.64 g (23.70 mmol) μ Al was added to 10 mL of anhydrous ethanol to form suspension B;
[0081] (S3) Pour suspensions A and B into a three-necked flask, maintain a constant temperature of 65°C in a water bath and stir for 10 min to form suspension C;
[0082] (S4) adding 0.6 g of sodium hydroxide to suspension C, stirring and reacting for 1 h to form suspension D;
[0083] (S5) 0.2 g of sodium hydroxide was added to the suspension D, and the mixture was stirred for reaction for 2 h, and then centrifuged, washed with anhydrous ethanol, and dried at 80° C. to obtain a core-shell structured nano-copper coated micro-aluminum.
[0084] Example 6
[0085] (S1) 2.06 g (7.87 mmol) of copper acetylacetonate was added to 10 mL of anhydrous ethanol to form a suspension A;
[0086] (S2) 0.64 g (23.70 mmol) μ Al was added to 10 mL of anhydrous ethanol to form suspension B;
[0087] (S3) Pour suspensions A and B into a three-necked flask, maintain a constant temperature of 75°C in a water bath and stir for 10 min to form suspension C;
[0088] (S4) adding 0.4 g of sodium hydroxide to suspension C, stirring and reacting for 1 h to form suspension D;
[0089] (S5) 0.4 g of sodium hydroxide was added to the suspension D, and the mixture was stirred for reaction for 2 h, and then centrifuged, washed with anhydrous ethanol, and dried at 80° C. to obtain a core-shell structured nano-copper coated micro-aluminum.
[0090] Example 7
[0091] (S1) 2.06 g (7.87 mmol) of copper acetylacetonate was added to 10 mL of anhydrous ethanol to form a suspension A;
[0092] (S2) 0.64 g (23.70 mmol) μ Al was added to 10 mL of anhydrous ethanol to form suspension B;
[0093] (S3) Pour suspensions A and B into a three-necked flask, maintain a constant temperature of 75°C in a water bath and stir for 10 min to form suspension C;
[0094] (S4) adding 0.3 g of sodium hydroxide to suspension C, stirring and reacting for 1 h to form suspension D;
[0095] (S5) 0.5 g of sodium hydroxide was added to the suspension D, and the mixture was stirred for reaction for 2 h, and then centrifuged, washed with anhydrous ethanol, and dried at 80° C. to obtain a core-shell structured nano-copper coated micro-aluminum.
[0096] Example 8
[0097] (S1) 2.06 g (7.87 mmol) of copper acetylacetonate was added to 10 mL of anhydrous ethanol to form a suspension A;
[0098] (S2) 0.64 g (23.70 mmol) μ Al was added to 10 mL of anhydrous ethanol to form suspension B;
[0099] (S3) Pour suspensions A and B into a three-necked flask, maintain a constant temperature of 75°C in a water bath and stir for 10 min to form suspension C;
[0100] (S4) 0.8 g of sodium hydroxide was added to the suspension C, and the mixture was stirred for reaction for 3 h, and then centrifuged, washed with anhydrous ethanol, and dried at 80° C. to obtain a core-shell structured nano-copper coated micro-aluminum.
[0101] Comparative Example 1
[0102] (S1) 2.06 g (7.87 mmol) of copper acetylacetonate was added to 10 mL of anhydrous ethanol to form a suspension A;
[0103] (S2) 0.64 g (23.70 mmol) μ Al was added to 10 mL of anhydrous ethanol to form suspension B;
[0104] (S3) Pour suspensions A and B into a three-necked flask, maintain a constant temperature of 75°C in a water bath and stir for 10 min to form suspension C;
[0105] (S4) The suspension C is washed with anhydrous ethanol, centrifuged, and dried at 80°C to obtain a product.
[0106] Performance Testing
[0107] The core-shell structure nano copper coated micron aluminum ( n Cu / μ Al) as samples.
[0108] The phase structure of the sample was analyzed by X-ray diffractometer to obtain the XRD spectrum, such as Figure 1 The red curve shows Figure 1 The green curve is from the standard phase card of copper, and the blue curve is from the standard phase card of aluminum. Figure 1 The XRD spectrum of the sample shows that θ =38.47°, 44.74°, 65.13°, 78.28°, and 82.44° all have diffraction peaks, which are characteristic diffraction peaks of aluminum; 2 θ =43.30°, 50.43°, and 74.13° are the characteristic peaks of elemental copper, respectively. These diffraction peaks are consistent with the standard cards of aluminum and copper, indicating that the entire coating process did not change the crystal form of aluminum. At the same time, these sharp diffraction peaks show that the composite aluminum powder has good crystallinity.
[0109] The microstructure of pure micron aluminum was observed using a field emission electron scanning microscope to obtain SEM images, such as Figure 2 shown. Figure 2 It shows that the surface of pure micron aluminum is a smooth spherical shape, and the surface is not covered by other substances (the smaller spherical particles appearing above are micron aluminum with smaller particle size).
[0110] The microstructure of the sample was observed using a field emission electron scanning microscope to obtain SEM images, such as Figure 3 shown. Figure 3 The sample particles are still spherical, and the surface of the aluminum ball is evenly covered with a large number of white balls, which are copper balls at the nano level. According to SEM testing, the spherical rate is above 95%. According to SEM testing, the thickness of the nano copper coating is 0.5 μ m, and its particle size is 0.02-3.24 μ m, particle size distribution is 1.6-2.8 μ m. According to the nitrogen adsorption and desorption test, the specific surface area of the core-shell structure nano-copper coated micron aluminum is 28.8 m 2 / g.
[0111] The thermal oxidation behavior of pure micron aluminum and samples was analyzed by differential scanning calorimetry, and the DSC curves were obtained, such as Figure 4Differential scanning calorimeter (DSC) test conditions: test temperature 50~1000℃, accuracy ±0.1℃, heating rate 10℃ / min, test atmosphere is air.
[0112] Figure 4 Display: Pure micron aluminum ( μ Al) has two oxidation exothermic peaks and one melting endothermic peak in the range of 50-1000℃. The two oxidation exothermic peaks are located at 603℃ and 927℃, respectively: the low-temperature oxidation exothermic peak of aluminum (617℃) and the high-temperature oxidation exothermic peak of aluminum (930℃). The melting endothermic peak is the melting endothermic peak of aluminum, located at 667℃. The total heat release of pure micron aluminum is 5.9kJ / g.
[0113] Figure 4 The results show that the sample has three oxidation exothermic peaks and one melting endothermic peak in the range of 50-1000℃. The three oxidation exothermic peaks are located at 253℃, 617℃, and 930℃, respectively: the oxidation exothermic peak of copper (253℃), the low-temperature oxidation exothermic peak of aluminum (617℃), and the high-temperature oxidation exothermic peak of aluminum (930℃). The melting endothermic peak is the melting endothermic peak of aluminum, located at 667℃. The total heat release of the sample is 16.72kJ / g.
[0114] according to Figure 4 It can be concluded that after coating, the oxidation heat release of the sample has been improved by 10.82 kJ / g, indicating that the thermal performance of the coated core-shell structure nano-copper coated micron aluminum is better.
[0115] Thermogravimetric analyzer was used to analyze the thermal oxidation behavior of pure micron aluminum and samples, and the active aluminum content was calculated according to the thermogravimetric method to obtain the TG curve, such as Figure 5 Thermogravimetric analyzer (TG) test conditions: test temperature is 50~1000℃, heating rate is 10℃ / min, and test atmosphere is air.
[0116] Figure 5 It shows that pure micron aluminum has two stages of weight gain in the range of 50-1000℃, namely low-temperature oxidation weight gain of aluminum and high-temperature oxidation weight gain of aluminum. The low-temperature oxidation weight gain of aluminum is 8%, the high-temperature oxidation weight gain of aluminum is 26%, the total oxidation weight gain of aluminum is 34%, and the active aluminum content calculated by thermogravimetric method is 38%.
[0117] Figure 5The results show that the sample has three weight gain stages within the range of 50-1000℃, namely, copper oxidation weight gain, aluminum low-temperature oxidation weight gain, and aluminum high-temperature oxidation weight gain; among them, copper oxidation weight gain is 18%, aluminum low-temperature oxidation weight gain is 14%, aluminum high-temperature oxidation weight gain is 39%, and aluminum oxidation weight gain is 53%. The active aluminum content calculated by thermogravimetry is 60%. Compared with the active aluminum content of pure micron aluminum, the active aluminum content of the sample has increased by 22%.
[0118] according to Figure 5 It can be concluded that the core-shell structure of nano-copper coated micron aluminum can further prevent the surface oxidation of aluminum and increase the active aluminum content, which is consistent with the above Figure 2 Morphology observed in SEM Figure 1 To.
[0119] The catalytic performance of the sample on pure ammonium perchlorate (AP) was analyzed by differential scanning calorimetry, and the DSC curve was obtained, as shown in Figure 6 Differential scanning calorimeter (DSC) test conditions: test temperature 50~500℃, accuracy ±0.1℃, heating rate 10℃ / min, test atmosphere air.
[0120] Figure 6 The two curves in the figure are the DSC curve of pure ammonium perchlorate (AP) and the DSC curve of the sample after adding it to AP ( n Cu / μ DSC curve of Al-AP). In the pure AP curve, the low-temperature oxidation exothermic peak and high-temperature oxidation exothermic peak of AP are 311°C and 422°C respectively; the low-temperature oxidation exothermic peak and high-temperature oxidation exothermic peak of AP after adding the sample are advanced to 295°C and 339°C respectively.
[0121] according to Figure 6 It can be concluded that adding samples to ammonium perchlorate (AP) advances the low-temperature and high-temperature decomposition peaks of AP, indicating that the addition of core-shell structured nano-copper coated micron aluminum has a good catalytic effect on AP. At the same time, the coating of transition metal copper effectively improves the problem of weak self-catalytic ability of aluminum powder.
[0122] The oxygen bomb calorimeter was used to test and calculate the combustion heat of pure micron aluminum powder and samples in pure oxygen. Oxygen bomb calorimeter: The test atmosphere is oxygen and the pressure is 1.2Mpa. After testing and calculation, the combustion heat of pure micron aluminum powder is 6kJ / g, and the combustion heat of the sample is 24kJ / g. Compared with pure micron aluminum powder, the combustion heat of core-shell structure nano copper coated micron aluminum is increased by 300%.
[0123] The microscopic morphology of the core-shell structured nano-copper coated micro-aluminum prepared in Example 7 was observed using a field emission electron scanning microscope to obtain a SEM image, as shown in FIG. Figure 7The microscopic morphology of the core-shell structured nano-copper coated micro-aluminum prepared in Example 8 was observed using a field emission electron scanning microscope to obtain a SEM image, as shown in FIG. Figure 8 The microscopic morphology of the product prepared in Comparative Example 1 was observed using a field emission electron scanning microscope to obtain a SEM image, as shown in FIG. Fig. 9 shown.
[0124] Figure 7 In the experiment, the spherical morphology of nano-copper-coated micron-aluminum particles is round, uniform, well-dispersed, with less agglomeration, and its copper coating is dense. Figure 8 There are a large number of copper particles and uncoated micron aluminum particles. The copper coating of the nano-copper-coated micron aluminum particles appears to be relatively loose, lacks density, and has a relatively irregular morphology. More agglomeration can be seen. Fig. 9 In the experiment, the rod-like structure is copper acetylacetonate, the granular structure is Al, the surface aluminum is not coated, and the copper ions are almost not reduced.
[0125] Compare Figure 7 and Figure 8 It can be seen that: Figure 8 compared to, Figure 7 The copper coating is denser, the particles are more uniform, the spherical morphology is rounder, the agglomeration is less, and the dispersion is better.
Claims
1. A method for preparing a core-shell structured nano-copper coated micron aluminum, characterized in that: The preparation method does not require the addition of additional reducing agents, complexing agents, surfactants or protective agents, and comprises the following steps: (S1) dispersing copper acetylacetonate in an organic solvent to obtain a suspension A; (S2) dispersing micron aluminum powder into an organic solvent to obtain a suspension B; (S3) Suspension A and suspension B are mixed and stirred at 35-75°C to form suspension C; (S4) maintaining 35-75° C., adding sodium hydroxide to the suspension C twice, stirring and reacting for 1-1.5 hours after the first addition of sodium hydroxide, and stirring and reacting for 2-2.5 hours after the second addition of sodium hydroxide, to form a suspension D; the amount of sodium hydroxide added for the first time accounts for 3 / 8-3 / 4 of the total amount of sodium hydroxide; (S5) centrifuging the suspension D, washing with alcohol, and drying to obtain the core-shell structured nano-copper coated micro-aluminum; the drying temperature is 65-80°C; The organic solvent used in the suspension A is one or more of anhydrous ethanol, ethylene glycol, and acetone; The organic solvent used in the suspension B is one or more of anhydrous ethanol, ethylene glycol and acetone.
2. The preparation method according to claim 1, characterized in that The mass ratio of the copper acetylacetonate to the micron aluminum powder is 1:0.3-0.
6.
3. The preparation method according to claim 1, characterized in that: In the suspension A, the mass ratio of the organic solvent to copper acetylacetonate is 1:0.05-0.
3.
4. The preparation method according to claim 1, characterized in that: In the suspension B, the mass ratio of the organic solvent to the micron aluminum powder is 1:0.04-0.
1.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the sodium hydroxide to the micron aluminum powder is 1:0.7-1.
3.
6. A core-shell structured nano-copper coated micron aluminum prepared by the preparation method according to any one of claims 1 to 5.
7. The core-shell structured nano-copper coated micron aluminum according to claim 6, characterized in that: The core of the core-shell structure nano copper coated micron aluminum particles is micron aluminum, and the shell is a nano copper coating layer; The core-shell structured nano copper-coated micron aluminum particles are spherical, with a sphericity rate of more than 95%; or / and, Compared with micron aluminum powder, the active aluminum content of the core-shell structure nano-copper coated micron aluminum is increased by 7%-22%; or / and, Compared with micron aluminum powder, the oxidation heat release of the core-shell structured nano-copper coated micron aluminum is increased by 7.44 kJ / g-10.82 kJ / g.
8. An application of the core-shell structured nano-copper coated micron aluminum prepared by the preparation method according to any one of claims 1 to 5 or the core-shell structured nano-copper coated micron aluminum according to claim 6 or 7 in the fields of solid rocket propellant, aerospace and military industry.
Citation Information
Patent Citations
Preparation method of nano-copper-coated aluminum composite fuel
CN108687359A